COMMUNICATIVE COMPETENCE OF PHYSICAL EDUCATION TEACHER - A DECISIVE FACTOR OF PROFESSIONAL SUCCESS - Frunză Gabriela (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
Communication competencies represent teacher's basic feature and mark the level of performance which ensures the efficiency of message transmission and reception. The purpose of pedagogical communication during physical education classes ensures the providing of communicative feedback within a teacher-student relationship. Communicative behavior changes are marked by student's results: cognitive, affective, behavioral. The experiment, based on questionnaire method, was conducted in 2 (two) stages and consisted of completing a self-assessment grid in which were included relevant items for communication skills that must be possessed by a physical education teacher, items such as: strategies for students' communication training, freedom of scientific expression, level of empathy, feedback level, synchronization of nonverbal with verbal communication, use of problematical questions for generating active communication situations, linking teaching strategy with communicating levels of students, active involvement of students in debates, dialogues, verbal modeling of learning situations that stimulate the success of applied interactive strategies, applying various communicative methods for creating opportunities for cooperation and competition during the class etc.